Solving Geometric Problems from the Perspective of Left and Right Brain Dominance - Kaliky, Syafruddin; Bachmid, Thaha; Hafeez, Muhammad (EDUPEDIA Publisher, 2025)
Problem-solving is an effort to find a way out of a difficulty so as to obtain a solution. Each child's problem-solving is different. This is influenced by the dominance of the brain in solving a problem. The purpose of this study is to describe the geometry problem-solving abilities of junior high school students in terms of left and right brain dominance. The research method is descriptive with a qualitative approach. The instruments used are test questions, questionnaires, and interview guidelines. The results show that students with left and right brain dominance types in solving geometry problems can fulfill all stages according to Gagne, which include Presentation of the problem, stating the problem in operational form, compiling work procedures, making hypotheses, and reviewing. The findings of students with left brain dominance in solving problems appear to be calmer and more patient, prefer to solve problems with formulas given by a teacher, need scratch paper in solving problems, tend to think with the chin supported by the right hand, and have neat writing. Meanwhile, students with right brain dominance in solving problems appear to move more, tend to have many ways, sometimes use their own way, work while speaking, and if they have scribbles, it will be very difficult to understand, and draw on blank paper with unclear images.